2014
DOI: 10.1111/vde.12125
|View full text |Cite
|
Sign up to set email alerts
|

Preferential gene transcription of T helper 2 cytokines in peripheral CCR4+CD4+ lymphocytes in dogs

Abstract: CCR4 can be used as a specific marker of Th2 cells for elucidation of the pathogenesis or the establishment of novel therapeutics in canine Th2-associated diseases, such as canine atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The relative quantity of st2 in CCR4 + CD4 + lymphocytes was approximately 14‐fold higher than that in CD4 + helper T cells ( P = 0.037; Figure b). In contrast, the transcription of st2 in CCR4 − CD4 + lymphocytes, which is more likely to include mostly Th1 cells, was under the detection limit (Figure b). Statistical analyses were not performed because the transcription of st2 was not observed in CCR4 − CD4 + lymphocytes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The relative quantity of st2 in CCR4 + CD4 + lymphocytes was approximately 14‐fold higher than that in CD4 + helper T cells ( P = 0.037; Figure b). In contrast, the transcription of st2 in CCR4 − CD4 + lymphocytes, which is more likely to include mostly Th1 cells, was under the detection limit (Figure b). Statistical analyses were not performed because the transcription of st2 was not observed in CCR4 − CD4 + lymphocytes.…”
Section: Resultsmentioning
confidence: 92%
“…In previous studies using human and murine cells, polarized Th2 cells that differentiated from naïve T cells in vitro were used to evaluate the expression of ST2 and the effects of IL‐33 on Th2 cells; however, these methods have never been established in dogs. One study demonstrated that CCR4 + CD4 + cells sorted from healthy dogs have the ability to produce Th2 cytokines including IL‐4 and IL‐13 in response to phorbol 12‐myristate 13‐acetate and calcium ionophores . Consequently, CCR4 + CD4 + cells were used as canine Th2 cells in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that subsets of Th cells selectively express chemokine receptors, such as CXC chemokine receptor (CXCR) 3 in Th1, CC chemokine receptor (CCR) 4 in Th2 or CCR6 in Th17 cells . In dogs, such distinct subsets of Th cells have not been reported; however, one study has demonstrated that CCR4 was selectively expressed in canine Th2 cells . In both humans and dogs, atopic skin lesions in the acute phase are characterized by Th2 cell‐dominant inflammation, suggesting that CCR4 plays a significant role in the trafficking of Th2 cells to lesional skin.…”
Section: Keratinocyte‐derived Cytokines and Chemokinesmentioning
confidence: 99%
“…TARC/CCL17 was cloned from humans in 1996 and from dogs in 2001, which shows 77.5% amino acid sequence similarity with the human orthologue . In both humans and dogs, TARC/CCL17 has been shown to be a functional ligand for CCR4, which is selectively expressed in Th2 cells . An initial study in dogs with cAD demonstrated the preferential transcription of tarc/ccl17 in atopic skin lesions, but not in nonlesional and healthy skin .…”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 99%
See 1 more Smart Citation